Leukemia Inhibitory Factor Induces Proopiomelanocortin via CRH/CRHR Pathway in Mouse Trophoblast - Wang, He; Sakata-Haga, Hiromi; Masuta, Hiroko; Tomosugi, Mitsuhiro; Tsukada, Tsuyoshi; Shimada, Hiroki; Sakai, Daisuke; Shoji, Hiroki; Hatta, Toshihisa (Frontiers in Cell and Developmental Biology, 2021)
We previously showed that maternal leukemia inhibitory factor (LIF) induces placental production of adrenocorticotropic hormone (ACTH), which stimulates fetal nucleated red blood cells to further secrete LIF and promote neurogenesis in rodent brains. However, the underlying mechanism of LIF-dependent ACTH induction remains unclear. Recently, we found that LIF induces corticotropin-releasing hormone (CRH) in mouse trophoblast stem cells. This finding supports the results of a previous study that CRH, which is produced by the placenta, induces placental ACTH production. In this study, we examined whether the effects of LIF are mediated by the induction of Pomc via CRH upregulation in mouse trophoblast. In vivo, protein levels of LIF and CRH peak in mouse placenta at 13.5 days post coitum. In mouse placenta, Crh mRNA and protein levels significantly increased 3 hours after intraperitoneal injection of LIF (5 μg/kg body weight) into dams at 13.5 days post coitum. We also examined the effect of LIF-induced CRH on the expression of Pomc induced by LIF in mouse trophoblast stem cells in vitro. After LIF supplementation for 3 days, we found that the increased expression of Crh-induced by new supplementation of LIF was earlier than that of Pomc. Furthermore, LIF-induced upregulation of Pomc in mouse trophoblast stem cells was attenuated by inhibition of the CRH/CRHR1 pathway, whereas LIF-induced secretion of ACTH was attenuated by inhibition of the JAK/STAT3 pathway. Therefore, LIF indirectly increases placental Pomc expression through the CRH/CRHR1 pathway, and placental ACTH secretion is induced directly by LIF via the JAK/STAT3 pathway.